Joy on demand : the art of discovering the happiness within - Tan, Chade-Meng (HarperOne, 2016)
"A long-awaited follow-up to the New York Times bestselling Search Inside Yourself shows us how to cultivate joy within the context of our fast-paced lives and explains why it is critical to creativity, innovation, confidence, and ultimately success in every arena. In Joy on Demand, Chade-Meng Tan shows that you don't need to meditate for hours, days, months or years to achieve lasting joy--you can actually get consistent access to it in as little as fifteen seconds. Explaining joy and meditation as complementary things that naturally reinforce each other, Meng explains how these two skills form a virtuous cycle, and once put into motion, become a solid practice that can be sustained in daily life. For many years, meditation has been taught and practiced in cultures where almost all meditators practice full-time for years, resulting in training programs optimized for practitioners with lots of free time and not much else to do but develop profound mastery over the mind. Seeing a disconnect between the traditional practice and the modern world, the bestselling author and Google's "Jolly Good Fellow" has developed a program, through "wise laziness," to help readers meditate more efficiently and effectively. Meng shares the three pillars of joy (inner peace, insight, and happiness), why joy is the secret is to success, and demonstrates the practical tools anyone can use to cultivate it on demand"--